Bioefficacy of different Insecticides against aphid (Myzus persicae) in cumin (Cuminum cyminum L.) - Hemant Swami, N L Dangi, M K Mahla, K C Ahir*, (Journal of Spices and Aromatic Crops, 2017)
A field trail was conducted in randomized block design at KVK Bhilwara, MPUAT, Udaipur to evaluate efficacy of carbosulfan 25% EC at 250, 312.5 and 375 g a.i. ha-1 along with thiamethoxam 25% WG at 25 g a.i. ha-1, imidacloprid 17.8 SL at 25 g a.i. ha-1 and acetamiprid 20% SP at 10 g a.i. ha-1 against aphid (Myzus persicae) in cumin during Rabi, 2013-14 and 2014-15. The result revealed that two sprays of carbosulfan 25% EC at 375 g a.i. ha-1 was found effective against aphid. It caused maximum mean reduction in thrips population after second spray at 10 days after application, which was 87.52% and 88.45% during 2013-14 and 2014-15, respectively. It was followed by carbosulfan 25% EC at 312.5 g a.i. ha-1. The maximum yields were recorded in case of carbosulfan 25% EC at 375 g a.i. ha-1, which were 622.3 and 456.7 kg ha-1 during 2013-14 and 2014-15, respectively and incremental yield of 358.6 kg ha-1 over untreated control.